2005
DOI: 10.1007/bf03018581
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Diclectin® reduces the incidence of postoperative vomiting

Abstract: B Ba ac ck kg gr ro ou un nd d: : Diclectin® (DCL) is an effective antiemetic used for relief of nausea and vomiting in pregnancy. It is unknown whether DCL is effective in the prevention of postoperative nausea and vomiting (PONV).M Me et th ho od ds s: : We conducted a randomized, stratified, double-blind placebo-controlled trial to examine the incidence of PONV in women undergoing elective laparoscopic tubal ligation in the day surgery setting. DCL (doxylamine succinate 10 mg and pyridoxine hydrochloride 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A recent Cochrane systematic review concluded that vitamin B 6 (pyridoxine) on its own may work, but the evidence for its efficacy for nausea associated with pregnancy is not very strong 1 . Other studies report it is most effective as part of a combination regimen 2, 3 . The need for an active comparator in general, and the choice of vitamin B 6 as the specific active comparator, were not adequately justified in this study.…”
Section: Commentarymentioning
confidence: 76%
“…A recent Cochrane systematic review concluded that vitamin B 6 (pyridoxine) on its own may work, but the evidence for its efficacy for nausea associated with pregnancy is not very strong 1 . Other studies report it is most effective as part of a combination regimen 2, 3 . The need for an active comparator in general, and the choice of vitamin B 6 as the specific active comparator, were not adequately justified in this study.…”
Section: Commentarymentioning
confidence: 76%
“…[2,9] Furthermore, vitamin B6 has been known to possess antiemetic effects since 1942. [3439] Hypotheses to describe the antiemetic effects of pyridoxine include prevention/treatment of vitamin B6 deficiency, intrinsic antinausea properties, and/or augmentation the antinausea properties of antihistamines. [3439] …”
Section: Discussionmentioning
confidence: 99%